Evaluation and quantification of treatment preferences for patients with asthma or COPD using discrete choice experiment surveys. (November 2017) - Svedsater, Henrik; Leather, David; Robinson, Terry; Doll, Helen; Nafees, Beenish; Bradshaw, Lisa
Abstract: Introduction: To investigate treatment preferences of patients with asthma or chronic obstructive pulmonary disease (COPD), previously identified influential treatment factors were used to develop a discrete choice experiment (DCE) survey. Methods: An internet-based survey was conducted with UK-resident adults (recruited using a commercial panel) who were currently receiving asthma/COPD treatment and had not taken part in the previous phase of this study (qualitative interviews to understand patient burden, life impact and treatment preferences). Participants ranked treatment attributes from 0 (extremely important) to 8 (not at all important) and chose between hypothetical treatments for asthma/COPD with differing attributes. Preferences for each condition were assessed separately using a mixed logit regression model. Results: Most of the 302 participants had not well-controlled asthma (Asthma Control Test™ scores ≤19/25) or experienced a high impact of COPD (COPD Assessment Test™ scores >20/40). Participant views were generally similar for both conditions; having well-controlled symptoms all day was considered most important. All treatment attributes significantly influenced preferences; the most preferred were no sleep disturbance (versus waking up often) and low cost. Subsequent preferences (with some variation between asthma/COPD) were for treatments with easy/convenient use, no flare ups/exacerbations, that enabled desired physical activities, well-controlled symptoms all day, that enabled desired social activities, and low medication frequency. Conclusions: These eight treatment attributes, valued by patients with asthma or COPD, are important for healthcare professionals to consider regarding treatment options and for future therapy development. Our DCE results broadly reinforce the findings from qualitative interviews in the first study phase. Highlights: Treatment preference in patients with asthma or COPD was assessed. Quantitative data were obtained from discrete choice experiment surveys. All eight investigated treatment attributes significantly influenced preferences. The most preferred treatment attribute was no sleep disturbance.